Screening of aflatoxin B1 and mycobiota related to raw materials and finished feed destined for fish - Carvalho Gonçalves Nunes, Etelvina María (2015)
The aim of the present study was to determine fungal genera, Aspergillus, Penicillium and Fusarium species and aflatoxin B1 contamination from raw materials and finished feed intended for fish farm localized in Piaui, Brazil. Aspergillus flavus and P. citrinum were isolated with a high relative density from all samples. In general, a high percent of samples exceeded the levels proposed as feed hygienic quality limits (CFU g -1 ) according to Good Manufacture Practice. Aflatoxin B1 was analyzed by enzyme-linked immunosorbent assay. All raw materials and finished feed showed aflatoxin B1 levels. Although in this study AFB1 levels below recommended limits (20 µg kg-1 ) were found, it is important to emphasize the feed intake with toxin in low concentrations along time, since it produce chronic deleterious effects in animal production. This fact requires periodic monitoring to prevent the occurrence of chronic aflatoxicosis in aquaculture, to reduce the economic losses and to minimize hazards to animal health.